Gambaran Keefektifan Komunikasi Tutor terhadap Warga Belajar Program Kesetaraan Paket C - Mulia, Wesi Okta; Solfema, Solfema (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the efficacy of the package C equality program in the Solok SKB SKNF, this was allegedly due to the effectiveness of the tutor's communication with the learning community. The aim of this research is to see the effectiveness of tutors' communication with the learning citizens of the Solok SKB SKB SPNF program equality seen from the aspect of people's understanding of learning, the enjoyment of learning citizens, the combination of tutors and learning citizens and the learning actions of tutors. This type of research is a quantitative descriptive. The population in this study was 37 people who studied the equivalence program package C SPNF SKB Kota Solok. The sampling technique used was stratified random sampling of 28 people. Data collection techniques used questionnaires. While the data collection tool is a questionnaire. The data analysis technique uses the percentage formula. The results showed that (1) the effectiveness of the tutor's communication with the learning community on the aspects of categorizing understanding was very effective, (2) the effectiveness of the tutor's communication with the learning aspects of the pleasure aspect was very effective, (3) the tutors' communication with the learning aspects the learning population is very effective, and (4) the effectiveness of the tutor's communication with the learning community on the aspects of learning citizens' actions is categorized as very effective.